Exossomas fundidos com lipossomas pH-sensíveis de circulação prolongada contendo doxorrubicina: preparo, caracterização, avaliação da toxicidade aguda e da atividade antitumoral. - Eliza Rocha Gomes (2022)
Doxorubicin (DOX) has a potent antineoplastic action and has been used in the treatment of several tumors. However, serious toxic effects have limited its use, especially cardiotoxicity. Recently, hybrid nanocarriers obtained by fusion of lipid membranes of exosomes and liposomes have been studied in order to increase antitumor efficacy, minimize adverse effects and overcome problems related to chemotherapy resistance. Thus, the purpose of this study was the fusion of exosomes derived from breast tumor cells with long-circulating and pH-sensitive liposomes containing DOX (ExoSpHL-DOX) for the treatment of breast cancer. The mean diameter of ExoSpHL-DOX was 100.8 ± 7.8 nm, the polydispersity index was 0.122 ± 0.004, and the encapsulated DOX content was equal to 83.5 ± 2.5%. The fusion of exosomes with long-circulating and pH-sensitive liposomes was confirmed by Fourier transform infrared spectroscopy, Raman spectroscopy, and nano-flow cytometry. The physicochemical characteristics of ExoSpHL-DOX were maintained for 60 days, at 4°C. The study of the release of DOX from ExoSpHL-DOX in dilution media with different pH values showed the pH-sensitivity of the nanosystem. The cytotoxic study against the 4T1 breast cancer cell line demonstrated that ExoSpHL-DOX treatment significantly reduced the cancer cell viability. Acute toxicity was determined by evaluating the mortality and morbidity of the animals, hematological, biochemical, and histopathological analyses, after a single intravenous administration of ExoSpHL-DOX. The results of the study indicated that the median lethal dose range (LD50) of the ExoSpHL-DOX treatment (17.5 - 20 mg/kg) is higher than that found for treatment with free DOX (12.5 - 15 mg/kg). In addition, ExoSpHL-DOX treatment showed no signs of nephrotoxicity even at the highest dose of DOX, indicating that the presence of hybrid nanocarrier may alter the distribution of DOX and reduce kidney damage. Regarding to the antitumor activity, ExoSpHL-DOX treatment inhibited close to 50% the tumor growth compared to control group. Furthermore, the hybrid nanocarrier of tumor-derived exosomes fused with long-circulating and pH-sensitive liposomes reduced the number of metastatic foci in the lungs. These results indicate that ExoSpHL-DOX may be a promising nanocarrier for the treatment of breast cancer, reducing toxicity and inhibiting metastasis, mainly in the lungs.